Cost-Effectiveness of Alirocumab for the Secondary Prevention of Cardiovascular Events after Myocardial Infarction in the Chinese Setting - Liang, Zhe; Chen, Qi; Wei, Ruiqi; Ma, Chenyao; Zhang, Xuehui; Chen, Xue; Fang, Fang; Zhao, Quanming (Frontiers in Pharmacology, 2021)
Background: Proprotein convertase subtilisin/kexin type 9 inhibitor alirocumab reduce ischemic events; however, the cost-effectiveness remains uncertain. This study sought to evaluate its economic value in patients with myocardial infarction (MI) from the Chinese healthcare perspective. Methods: A state-transition Markov model was developed to determine the cost-effectiveness of alirocumab for preventing recurrent MI, ischemic stroke and death. Preventative effect of the therapy was gathered from ODYSSEY OUTCOMES trial and absolute reduction of low-density lipoprotein cholesterol (LDL-C) in ODYSSEY EAST trial, respectively. The primary outcome was the incremental cost-effectiveness ratio (ICER), defined as incremental cost per quality-adjusted life-year (QALY) gained. Results: Compared with statin monotherapy, the ICER of alirocumab therapy at its present discounted price [34,355 Chinese yuan (CNY) annually, 33% rebate] based on clinical follow-up efficacy was 1,613,997 CNY per QALY gained. A willingness-to-pay threshold of 212,676 CNY per QALY would be achieved when the annual cost of alirocumab was reduced by 88% from the full official price to 6071 CNY. The therapeutic effect evaluation estimated by the magnitude of LDL-C reduction was superior to the results of clinical follow-up, but this medication was still far from cost-effective. Multiple vulnerable subgroup analyses demonstrated that the ICER for patients with polyvascular disease in 3 vascular beds was 111,750 CNY per QALY gained. Conclusion: Alirocumab is not cost-effective in general MI population based on current discounted price. High long-term costs of alirocumab may be offset by health benefit in patients with polyvascular disease (3 beds).